Retrospective analysis of abandoned live births, stillbirths and non-viable foetuses admitted to Salt River Mortuary, Cape Town - du Toit, Chante (Department of Pathology, 2019)
The abandonment of neonates in locations where discovery and survival is not intended is a global concern. These cases comprise non-viable foetuses and stillbirths (natural deaths), as well as abandoned live births (unnatural deaths); the latter having possible legal consequences. To describe the profile of abandoned neonates and obtain a global perspective of the post-mortem investigation in such cases, a systematic review of the literature on abandoned foetuses, concealed births and neonaticide was conducted. This revealed a paucity of research on the subject; only one published South African study and less than 30 studies from other parts of the world were obtained. While guidelines were available, a standard protocol for conducting the medico-legal investigation on abandoned neonates did not exist and the necessary extent of the investigation was debated. Furthermore, seemingly higher rates of abandoned neonates were observed in South Africa compared to elsewhere in the world, warranting investigation of these cases in a local setting. In an attempt to add to the data concerning abandoned neonates in South Africa, a case file review was carried out on abandoned live births, stillbirths and non-viable foetuses at Salt River Mortuary between 1 January 2012 and 31 December 2016 (n=249). Despite the majority of the cases being natural deaths, the cause of death frequently remained 'undetermined’ in these cases, often due to the presence of decomposition. Histological analyses were only performed in a small fraction of undetermined cases. Furthermore, the hypothesis that the prosecution rate of abandoned live births is extremely low was supported by this study, with only one case prosecuted in the 5- year period. For the remainder of the cases, the court status was given as either 'under investigation’ (47.8%) or 'case closed’ (47.8%). In the majority of the instances, the case was closed due to the unknown identity of the biological mother; however, DNA analyses were not performed in all of these cases. Overall, the data highlighted the need for the development and implementation of standard protocols, to ensure that cause of death and identification of the neonate can be established as far as possible.